STRUCTURE AND SPATIOTEMPORAL HETEROGENEITY OF BIRD SUMMER POPULATION IN DAGESTAN HIGH MOUNTAINS (BY EXAMPLE OF CHARODINSKY DISTRICT) - Ye. V. Vilkov (Юг России: экология, развитие, 2014)
The paper deals with the study of a structure and formation peculiarities of spatial connections of birds in two different biotopic natural complexes in one of Dagestan high mountain districts – Charodinsky (at the altitude interval of 2000-2300 m). Biotopic heterogeneity of the ornithological population has made it possible to single out and give an elaborate description of 10 differentiated ornithological complexes which represent the actual correlation between background landscape types. It has been established that the avifauna structure in Dagestan high-mountain areas includes 8 fauna-genetic groups of birds making local ecological micro-pulations as members of widely spread species typical of lowlands, mountain fauna and Caucasian endemics. We suggest that local population of migrating birds in high mountains is formed of local (high-mountain) ecologically adapted micropopulations and as well replenished by their own offspring. At present the structure of the high-mountain avifauna may undergo certain changes owing to global warming and ever rising anthropogenic load accompanied by destruction of natural landscapes.